The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/acm2.13866
|View full text |Cite
|
Sign up to set email alerts
|

Calculating dose‐averaged linear energy transfer in an analytical treatment planning system for carbon‐ion radiotherapy

Abstract: Background Compelling evidence shows the association between the relative biological effectiveness (RBE) of carbon‐ion radiotherapy (CIRT) and the dose averaged linear energy transfer ( LETd ). However, the ability to calculate the LETd in commercially available treatment planning systems (TPS) is lacking. Purpose This study aims to develop a method of calculating the LETd of CIRT plans tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The accuracy of the simulation to measurements may be a source of uncertainty. Our previous study demonstrated that the fragment spectra in RayStation overestimated the LET distally compared to the fragment spectra in Syngo [ 34 ]. Moreover, the different types of MC toolkits may be another reason.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the simulation to measurements may be a source of uncertainty. Our previous study demonstrated that the fragment spectra in RayStation overestimated the LET distally compared to the fragment spectra in Syngo [ 34 ]. Moreover, the different types of MC toolkits may be another reason.…”
Section: Discussionmentioning
confidence: 99%
“…The CIRT LET d in patients was calculated according to our approach. 12 The conversion from LET d to OER was based on a systematic study using CHO cells. 13 Equation ( 1 ) is displayed as follows: where p O 2 is the tumor oxygen level.…”
Section: Methodsmentioning
confidence: 99%
“…The CIRT LET d in patients was calculated according to our approach 12 . The conversion from LET d to OER was based on a systematic study using CHO cells 13 .…”
Section: Methodsmentioning
confidence: 99%